Higher general executive functions predicts lower body mass index by mitigating avoidance behaviors - La Marra, Marco; Ilardi, Ciro Rosario; Villano, Ines; Polito, Rita; Sibillo, Maria Raffella; Franchetti, Marina; Caggiano, Angela; Strangio, Francesca; Messina, Giovanni; Monda, Vincenzo; Di Maio, Girolamo; Messina, Antonietta (Frontiers in Endocrinology, 2022)
Background The present study examines the relationship between obesity, executive functions, and body image in a nonclinical population from southern Italy. Methods General executive functioning (Frontal Assessment Battery–15), and body image disturbances (Body Uneasiness Test) were assessed in a sample including 255 participants (138 females, M age = 43.51 years, SD = 17.94, range = 18–86 years; M body mass index (BMI) = 26.21, SD = 4.32, range = 18.03–38.79). Findings Multiple Linear Regression Analysis indicated that age, years of education, FAB15 score, body image concerns, and avoidance predicted the variance of BMI. A subsequent mediation analysis highlighted that the indirect effect of FAB15 on BMI through avoidance was statistically significant. Interpretation Our results suggest that more performing executive functioning predicts a decrease in BMI that is partially due to the mitigation of avoidance behaviors.